1999
DOI: 10.1590/s0104-14281999000300006
|View full text |Cite
|
Sign up to set email alerts
|

Processo de obtenção de pré-impregnados poliméricos termoplásticos via moldagem por compressão a quente

Abstract: Os compósitos poliméricos à base de termoplásticos avançados são usados em aplicações estruturais devido à uma combinação favorável de baixa massa específica e desempenho mecânico elevado. Uma das rotas para o processamento desses compósitos é via laminação e consolidação adequadas de pré-impregnados poliméricos termoplásticos. Este trabalho apresenta o estudo da obtenção de pré-impregnados termoplásticos via moldagem por compressão a quente, mostrando os parâmetros temperatura e pressão utilizados no processa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…Aromatic imide thermoplastic polymers, such as PEI, have been candidates for a variety of applications due to its excellent properties, such as flexibility, high glass transition temperature, excellent thermal stability/fire retardance, and ultraviolet radiation resistance. [24][25][26][27] Many studies have reported that only small addition of CNT in polymers can improve the thermal stability of composites significantly, resulting in an increase of thermal decomposition temperatures by about 5-10 C. [28][29][30] In addition, there are several models that explain the thermal decomposition of solids based on different theoretical concepts and empirical studies. In this study, the integral model of O-W-F was chosen because it is a widely used method in the thermal decomposition of polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic imide thermoplastic polymers, such as PEI, have been candidates for a variety of applications due to its excellent properties, such as flexibility, high glass transition temperature, excellent thermal stability/fire retardance, and ultraviolet radiation resistance. [24][25][26][27] Many studies have reported that only small addition of CNT in polymers can improve the thermal stability of composites significantly, resulting in an increase of thermal decomposition temperatures by about 5-10 C. [28][29][30] In addition, there are several models that explain the thermal decomposition of solids based on different theoretical concepts and empirical studies. In this study, the integral model of O-W-F was chosen because it is a widely used method in the thermal decomposition of polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…Esta técnica garante compósitos com boa qualidade superficial e permite o uso de reforços com diferentes geometrias. Este método é principalmente utilizado no processamento de polímeros termorrígidos, como as resinas fenólicas, melamínicas, epoxídicas e as borrachas [1,2]. No caso da moldagem por compressão a quente, grandes esforços são utilizados na prensagem do material na cavidade, associados às temperaturas na faixa de 100 a 300 °C.…”
Section: Introductionunclassified
“…In general, thermoplastic composites with continuous fibers are produced with less processing cycles, and can be hot pressed, thermoformed, pultruded, consolidated in autoclave or by automated methods on multiple complex shapes of large size [14][15][16][17][18][19][20] . Besides, they can be welded to other structures by electrical resistance, ultrasonic and induction technologies, for example [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%